2014
DOI: 10.1063/1.4879898
|View full text |Cite
|
Sign up to set email alerts
|

Coercivity enhancement in Dy-free Nd–Fe–B sintered magnets by using Pr-Cu alloy

Abstract: The grain boundary phase of Dy-free sintered Nd-Fe-B magnets is modified by using Pr 68 Cu 32 eutectic alloy. The coercivity of the modified magnets reaches 21 kOe, which is the highest value in Dy-free Nd-Fe-B sintered magnets. Microstructural investigations show that a smooth and thick grain boundary layer is formed, and the content of the ferromagnetic elements in the grain boundary layer decreases from 65 at. % to 9 at. %. In addition, the mean grain size (4.5 lm) in the doped sintered magnets is smaller t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The nonferromagnetic RE-rich GB phase can decouple the ferromagnetic grains well, hence enhancing the coercivity [12,13]. The content of Fe and RE in some regions were observed, as marked by blue crosses in Fig.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The nonferromagnetic RE-rich GB phase can decouple the ferromagnetic grains well, hence enhancing the coercivity [12,13]. The content of Fe and RE in some regions were observed, as marked by blue crosses in Fig.…”
Section: Resultsmentioning
confidence: 84%
“…This approach requires highly airtight facilities and environments to avoid oxidation of the extremely fine Nd-Fe-B powders (less than 1 μm), which is still challenging for handling such ultrafine RE alloy powders in industrial system. More recently, utilizing the industrial powder metallurgy method, a much higher coercivity of 21 kOe is realized in a Dy-free Nd 12.2 Pr 2.6 Fe 76.3 Co 2.1 B 6.0 Nb 0.2 Al 0.5 Cu 0.1 sintered magnet with an mean grain size of $4.5 μm [13]. The high coercivity was achieved by forming thick layer nonferromagnetic RE-rich GB phase to decouple the large grains with 20 wt% Pr-Cu alloy modification.…”
Section: Introductionmentioning
confidence: 99%
“…Amin and Murakami et al have suggested that forming thick grain boundaries (GBs) with low content of ferromagnetic elements is an effective method to weaken the inter-grain coupling and enhance the coercivity of Nd-Fe-B sintered magnets [2,17]. By increasing the thickness of the GBs above 20 nm with the content of ferromagnetic elements (Fe + Co) below 9 at.%, coercivity as high as 21.0 kOe has been obtained in the Dy-free magnet [18]. Unlike the ultrafine-grained magnet that requires careful control of the oxygen atmosphere through PLP approach, this magnet is prepared by conventional powder metallurgy route with intergranular addition of 20 wt.% Pr 68 Cu 32 .…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, it was doped at a much lower level than Pr 68 Cu 32 in ref. 18 to reduce the total RE content. Aside from forming thick GBs, it is also expected to form (Nd, Ho) 2 Fe 14 B shells to enhance the magnet H A .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these efforts mainly focus on coercivity enhancement technology, new processing and properties of Nd-Fe-B magnet, RE magnet recycle technology and RE free magnet, In terms of coercivity enhancement technology, typical research focus on manipulating and improving the microstructure either via grain boundary diffusion process 12,13 or via multi-alloy process, [14][15][16] by which the coercivity of sintered Nd-Fe-B magnet can be increased significantly. As for the development of new processing and properties of Nd-Fe-B magnet, one effective way worth to mention is the hot deformed nanocrystalline magnets with excellent magnetic properties prepared by die-upset process.…”
Section: Other Permanent Magnetic Materials Randd Activities In Chinamentioning
confidence: 99%